The The Moderating Effect of Company Size on Audit Committee and Intelectual Capital Toward Corporate Value - Simandjuntak, JBP; Murwaningsari, Etty (Archives of Business Research, 2022)
In this study, to analyze the effect of Audit Committee, and Intelectual Capital toward Company values. And also analyzes the impact of Company Size as a moderating variable that strengthens or weakens the relationship between the effects of Audit Committee, Intecetual capital toward Company values. The researcher collects empirical study data from the companies using secondary data taken from the annual reports of companies listed on the Indonesia Stock Exchange (IDX). This study used a purposive sampling technique and obtained as many as 53 companies in accordance with predetermined criteria. Then analyzes them using the Statistical Package for the Social Sciences. A total of 265 units of data analysis that meet the criteria and can be used as samples in this study. This study only takes secondary data from the annual reports of company’s in the Indonesia stock exchange. Company Size as a moderator between Audit Committee and Intellectual Capital toward Corporate Value in companies listed on the Indonesia Stock Exchange is still little researched. So this research will not only fill in the current gaps in the literature but also spark new academic debates, but this study will also contribute to the practice of Corporate Value. This study reveals that Audit Commitee and Intellectual Capital have a positive and significant effect on Corporate Value. Meanwhile, the role of the Company Size as a moderating variable have strengthens the influence between Audit Commitee and Corporate Value from before being moderated by the Company Size.